Aesthetics and morality judgments share cortical neuroarchitecture. (August 2020) - Heinzelmann, Nora C.; Weber, Susanna C.; Tobler, Philippe N.
Abstract: Philosophers have predominantly regarded morality and aesthetics judgments as fundamentally different. However, whether this claim is empirically founded has remained unclear. In a novel task, we measured brain activity of participants judging the aesthetic beauty of artwork or the moral goodness of actions depicted. To control for the content of judgments, participants assessed the age of the artworks and the speed of depicted actions. Univariate analyses revealed whole-brain corrected, content-controlled common activation for aesthetics and morality judgments in frontopolar, dorsomedial and ventrolateral prefrontal cortex. Temporoparietal cortex showed activation specific for morality judgments, occipital cortex for aesthetics judgments. Multivariate analyses revealed both common and distinct whole-brain corrected representations for morality and aesthetics judgments in temporoparietal and prefrontal regions. Overall, neural commonalities are more pronounced than predominant philosophical views would predict. They are compatible with minority accounts that stress commonalities between aesthetics and morality judgments, such as sentimentalism and a valuation framework.